Black Thyroid Associated with Thyroid Carcinoma - Emad Kandil; Mohamed Abdel Khalek; Haytham Alabbas; Philip Daroca; Tina Thethi; Paul Friedlander; Ryan Leblanc; Obai Abdullah; Bernard Jaffe; Byron Crawford (International Journal of Endocrinology)
Objective. Black thyroid is a rare pigmented change seen almost exclusively in patients upon minocycline ingestion, and the process has previously been thought to be generally benign. There have been 61 reported cases of black thyroid. We are aware of 13 cases previously reported in association with thyroid carcinoma. This paper reports six patients with black thyroid pigmentation in association with thyroid carcinoma. Design. The medical records of six patients who were diagnosed with black thyroid syndrome, all of whom underwent thyroid surgery, were reviewed. Data on age, gender, race, preoperative fine needle aspiration biopsy (FNA), thyroid function levels, and pathology reports were collected. Main Outcome. The mean age was 60 years. There were 5 females, 4 of whom were African American. All patients were clinically and biochemically euthyroid. Black pigmentation was not diagnosed in preoperative FNA, and only one patient had a preoperative diagnosis of papillary thyroid carcinoma. The other patients underwent surgery and were found to have black pigmentation of the thyroid associated with carcinoma. Conclusions. FNA does not diagnose black thyroid, which is associated with thyroid carcinoma. Thyroid glands with black pigmentation deserve thorough pathologic examination, including several sections of each specimen.